2017
DOI: 10.1021/acs.langmuir.7b01777
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Coated Core–Shell Structured Polystyrene Nanospheres and Their Size-Dependent Mechanical Properties

Abstract: The core-shell structured PS/SiO composite nanospheres were synthesized on the basis of a modified Stöber method. The mechanical properties of monodisperse nanospheres were characterized with nanoindentation on the basis of the atomic force microscopy (AFM). The surface morphologies of PS/SiO composite nanospheres was scanned with the tapping mode of AFM, and the force-distance curves were measured with the contact mode of AFM. Different contact models were compared for the analyses of experimental data. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…The soap-free emulsion polymerization was applied to prepare the PS/OMMT nanocomposites according to previous reports [24,25]. Briefly, a mixture of OMMT (0.6 g, 3.0 wt % based on St), St (20.0 g), DVB (1.8 g) and an auxiliary monomer MAA (1.0 g) was ultrasonicated for 10 min in an ice bath and then magnetically stirred at room temperature for 1 h (Figure 1 (Stage D)).…”
Section: Methodsmentioning
confidence: 99%
“…The soap-free emulsion polymerization was applied to prepare the PS/OMMT nanocomposites according to previous reports [24,25]. Briefly, a mixture of OMMT (0.6 g, 3.0 wt % based on St), St (20.0 g), DVB (1.8 g) and an auxiliary monomer MAA (1.0 g) was ultrasonicated for 10 min in an ice bath and then magnetically stirred at room temperature for 1 h (Figure 1 (Stage D)).…”
Section: Methodsmentioning
confidence: 99%
“…The group of Yan turns their attention to the field recently using an atomic force microscope (AFM) with a peakforce quantitative nanoscale mechanical (QNM) mode. [306][307][308] The nano/micromechanical plays a significant role in flexible and stretchable devices, such as the triboelectric nanogenerator. 223 Moreover, integration of the colloidal-based surface patterning with other lithography/patterning methods may be widely applied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as previously reported, porous silica abrasives turn out to be a better choice than conventional solid spheres due to their superior surface-flattening and damage-eliminating abilities, which can be attributed to their preferable elastic deformation ability [43,46,47]. In fact, the dependence of E values on porous silica shell thicknesses in the core-mesoporous shell structured composites has been largely vindicated in some literatures [48][49][50]. Moreover, Jauffrès et al [51] concluded employing nanoindentation and finite element model that mesoporous thin silica films with a lattice-ordered porosity exhibit a higher indentation modulus and a more elastic recovery behavior relative to random macroporous ones.…”
Section: Introductionmentioning
confidence: 88%